Role of anti‐domain 1‐β2glycoprotein I antibodies in the diagnosis and risk stratification of antiphospholipid syndrome. (24th August 2016) - De Craemer, A.‐S.; Musial, J.; Devreese, K. M. J.
Abstract : Essentials Antibodies to domain 1 of β2 glycoprotein I (aD1) are a subset of antiphospholipid antibodies. We evaluated the added diagnostic value of an automated aD1 assay in antiphospholipid syndrome. AD1 IgG correctly classifies patients at risk for thrombosis. Agreement between aD1 and aβ2GPI IgG is high, limiting the added value of aD1 in our setting. Click to hear Professor de Groot's perspective on new mechanistic understanding in antiphospholipid syndrome Summary: Background: Laboratory diagnosis of antiphospholipid syndrome (APS) includes lupus anticoagulant (LAC), anticardiolipin (aCL) or anti‐β2 glycoprotein I (aβ2 GPI) antibodies. Antibodies targeting domain 1 of β2 GPI (aD1) constitute a pathogenic subset of autoantibodies. Objectives: In this cohort study, we determined the clinical performance characteristics, additional diagnostic value and the contribution to APS risk stratification of an automated aD1 assay. Patients/Methods: LAC, aCL, aβ2 GPI and aD1 IgG were measured in 101 APS patients, 123 patients with autoimmune disorders, 82 diseased controls and 120 healthy controls. aD1 antibodies were detected by QUANTA Flash ® Beta2GPI‐Domain 1 chemiluminescence immunoassay. Results: With a cut‐off value of 20.0 CU, the aD1 IgG assay identifies APS patients in a clinically affected patient cohort with a sensitivity of 53.5% and specificity of 98.8%. It implied a high odds ratio (OR) for clinical events (OR, 17.0; 95% confidence interval [CI], 7.1–40.5). aD1 IgG did not add diagnostic value to the formal aPL panel because aβ2 GPI IgG was nearly as specific but more sensitive for APS (sensitivity 56.4%) with a higher OR for clinical events (36.2; 95% CI, 11.1–117.9). High aD1 titers identify triple‐positive patients and patients with thrombosis in a β2 GPI‐dependent LAC‐positive population. Agreement between aD1 IgG and aβ2 GPI IgG was high (positive and negative agreement 91.7% and 98.4%, respectively). Conclusion: Detection of aD1 IgG correctly classifies patients at risk of thrombosis. However, the contribution of aD1 IgG to APS diagnosis and risk stratification depends upon the solid phase assays used for aCL and aβ2 GPI detection.